2022
DOI: 10.3390/safety8020030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Automation and Fatigue on Drivers from Various Age Groups

Abstract: This study explores how drivers are affected by automation when driving in rested and fatigued conditions. Eighty-nine drivers (45 females, 44 males) aged between 20 and 85 years attended driving experiments on separate days, once in a rested and once in a fatigued condition, in a counterbalanced order. The results show an overall effect of automation to significantly reduce drivers’ workload and effort. The automation had different effects, depending on the drivers’ conditions. Differences between the manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The dynamics of the lead car and ego car equations are similar which is a transformation from vehicle's acceleration into speed and position. The dynamic equation for the two vehicles can be written in equation (1), which shows the relationship between acceleration as input and speed as an output transfer function.…”
Section: System Model Accmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of the lead car and ego car equations are similar which is a transformation from vehicle's acceleration into speed and position. The dynamic equation for the two vehicles can be written in equation (1), which shows the relationship between acceleration as input and speed as an output transfer function.…”
Section: System Model Accmentioning
confidence: 99%
“…The application of automation in recent automotive industries is becoming a necessity. It is intended for several reasons such as reducing fatigue while driving [1], [2], increasing driver safety [3] [4], vehicle fuel efficiency [5] [6], and making it simpler for drivers to park their vehicles [7] [8]. Another case can also be shown from vehicle platooning to reduce greenhouse gas emissions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many validation studies for PERCLOS have been conducted, particularly in the context of driving, with numerous simulation studies reporting increases in PERCLOS or %TEC during driving after sleep deprivation [ 57 , 67 , 70 ] or partial sleep deprivation [ 59 ], overnight driving [ 65 , 71 , 89 ], driving after a night shift [ 53 ], driving at post-lunch dip [ 53 ], driving during sleep inertia [ 90 ], driving after benzodiazepine administration [ 81 ], or automated driving (combined operation of adaptive cruise control and lane-keeping assistance) when compared to manual driving [ 91 ]. The effect of automated driving on PERLOS is more pronounced under fatigued conditions (extended wakefulness or sleep deprivation) [ 91 ]; PERCLOS has been shown to increase with self-reported sleepiness during simulated driving [ 57 , 90 , 92 ]. On-road driving studies have also reported increases in PERCLOS during manual driving with sleep deprivation in younger adults [ 72 ], during nurses’ commutes after a night shift compared to before a night shift [ 93 ], and during motorway driving at night time [ 94 ].…”
Section: Use Of Perclos Under Various Driving Conditionsmentioning
confidence: 99%
“…Third, there may be limitations to using PERCLOS for detecting drowsiness in older adults. Studies have shown that PERCLOS in older adults does not always correspond to underload in automated simulated driving compared to manual driving [ 91 ] or deterioration in on-road performance due to sleep deprivation [ 72 ]. In the latter study, older drivers showed increased lane deviation as a result of sleep deprivation, suggesting that factors other than falling asleep, such as inattention and distraction related to drowsiness [ 98 ], may contribute to impairments in driving performance due to drowsiness.…”
Section: Use Of Perclos Under Various Driving Conditionsmentioning
confidence: 99%
See 1 more Smart Citation